Systematic Literature Review: The Implementation of Smart Manufacturing to Enhance Production Process Efficiency - Taryana Taryana (Journal of Renewable Engineering, 2026)
The emergence of smart manufacturing in the Industry 4.0 era has transformed traditional production systems into interconnected, data-driven environments aimed at enhancing efficiency and flexibility. However, conventional manufacturing systems continue to face challenges such as planning errors, bottlenecks, machine downtime, and limited technological integration. This study aims to systematically analyze the implementation of smart manufacturing technologies in improving production process efficiency. The research employs a systematic literature review (SLR) with a qualitative approach, utilizing secondary data from peer-reviewed journals and academic publications. Data collection follows structured stages of identification, screening, eligibility, and inclusion, while data analysis is conducted through thematic and content analysis to identify patterns, technologies, and efficiency outcomes. The findings reveal that key technologies such as Cyber-Physical Systems (CPS), Internet of Things (IoT), Artificial Intelligence (AI), big data analytics, and digital twins significantly contribute to improving production efficiency through real-time monitoring, predictive maintenance, and optimized decision-making. These technologies effectively reduce downtime, minimize waste, and enhance overall system performance. In conclusion, smart manufacturing represents a transformative approach that addresses inefficiencies in conventional systems and supports sustainable industrial development through integrated and intelligent production processes.